The Transmural Trauma Care Model (TTCM) for the rehabilitation of trauma patients is effective in improving patient related outcome measures: a non-randomized controlled trial - Suzanne H. Wiertsema; Johanna M. van Dongen; Edwin Geleijn; Heleen Beckerman; Frank W. Bloemers; Raymond W. J. G. Ostelo; Vincent de Groot (BMC, 2019)
Abstract Background The Transmural Trauma Care Model (TTCM) is a refined post-clinical rehabilitation approach, in which a multidisciplinary hospital-based team guides a network of primary care physical therapists in the treatment of trauma patients. The objective of this study was to assess the effectiveness of the TTCM compared to regular care. Methods A controlled-before-and-after study was performed in a level 1 trauma center. The TTCM includes four elements: 1) a multidisciplinary team at the outpatient clinic, 2) coordination and individual goal setting for each patient by this team, 3) a network of primary care physical therapists, 4) E-health support for transmural communication. Intervention group patients were prospectively followed (3, 6 and 9 months). The control group consisted of 4 clusters of patients who either had their first consultation at the outpatient clinic 0, 3, 6 or 9 months ago. Outcomes included generic- and disease-specific health-related quality of life (HR-QOL), pain, functional status, patient satisfaction, and perceived recovery. Between-group comparisons were made using linear regression analyses. The recovery pattern of intervention group patients was identified using longitudinal data analysis methods. Results A total of 83 participants were included in the intervention group. In the control group, 202 participants were included (68 in the baseline cluster, 26 in the 3-month cluster, 51 in the 6-month cluster, 57 in the 9-month cluster). Between-group differences were statistically significant in favor of the intervention group for disease-specific HR-QOL at 9 months, pain at 6 and 9 months, functional status at 6 and 9 months, patient satisfaction at 3, 6 and 9 months, and perceived recovery at 6 months. No significant differences were found between groups for generic HR-QOL at any time point. Generic HR-QOL, disease-specific HR-QOL, pain, and functional status significantly improved in a linear fashion among intervention group patients during the nine-month follow-up period. Conclusions This study provides preliminary evidence that the TTCM is effective in improving patient related outcome measures, such as disease-specific HR-QOL, pain and functional status. A multicenter, and ideally randomized controlled trial, is required to confirm these results. Trial registration The trial is registered at the Dutch Trial Register (NTR5474). Registered 12 October 2015. Retrospectively registered.